2014
DOI: 10.1074/jbc.m113.538470
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Activation of the Human Epithelial Sodium Channel by Trypsin IV and Trypsin I Involves Distinct Cleavage Sites

Abstract: Proteolytic channel activation is a unique feature of the epithelial sodium channel (ENaC) but is not yet fully understood. The serine protease trypsin is known to activate ENaC in vitro but may not be relevant in vivo. In this study, we wanted to investigate whether the trypsin‐like serine protease trypsin IV, known to be expressed in several epithelial tissues, can activate human ENaC. Moreover, using site‐directed mutagenesis we wanted to identify functionally relevant cleavage sites in the γ‐subunit of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 46 publications
3
40
1
Order By: Relevance
“…Importantly, we showed that plasmin concentrations in the range of those observed in urine samples of patients with CKD were sufficient to activate ENaC currents in vitro. In previously published studies, higher plasmin concentrations have been used to show its activating effect on ENaC (9,10,24,25). However, the exposure time to plasmin in those studies was relatively short (5-30 minutes), whereas in this study, plasmin at comparatively low concentrations showed a stimulating effect on ENaC after 4 hours of exposure.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…Importantly, we showed that plasmin concentrations in the range of those observed in urine samples of patients with CKD were sufficient to activate ENaC currents in vitro. In previously published studies, higher plasmin concentrations have been used to show its activating effect on ENaC (9,10,24,25). However, the exposure time to plasmin in those studies was relatively short (5-30 minutes), whereas in this study, plasmin at comparatively low concentrations showed a stimulating effect on ENaC after 4 hours of exposure.…”
Section: Discussioncontrasting
confidence: 48%
“…Oocytes were collected from Xenopus laevis with the approval of the animal welfare officer for the University of Erlangen-Nürnberg as described (7,9,10). Defolliculated stages 5 and 6 oocytes were injected with complementary RNA encoding human a-, b-, and g-ENaC (0.2 ng complementary RNA per subunit of ENaC).…”
Section: Two-electrode Voltage Clamp Measurements Using Human Enac-exmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, trypsin at low concentrations was reported to stimulate membrane‐resident ENaCs in Xenopus oocytes via G‐protein–coupled receptors distinct from PARs . In contrast, direct action of trypsin involving proteolytic cleavage of α‐ENaC and γ‐ENaC subunits was observed on ENaCs expressed in 3T3 cells or X. oocytes . Consistently, extracellular proteases were concluded to stimulate ENaC channels in native renal mouse tubules and cultured M‐1 cortical collecting duct cells .…”
Section: Discussionmentioning
confidence: 88%